Análisis retrospectivo de los últimos 10 años de las principales patologías reproductivas que afectan a la ganadería de leche en Colombia (2021)
The objective of this study was to determine the prevalence of the main pathologies with reproductive impact in Colombian dairy cattle that cause great economic losses, due to the amount of etiological agents that could be innumerable and therefore those that have more relevance were mentioned. in our midst. Among them are, Bovine Viral Diarrhea (BVD), Infectious Bovine Rhinotracheitis (IBR), Leptospirosis, Neosporosis and Brucellosis, these are the most frequent pathologies in Colombia of viral, bacterial and parasitic origin respectively that affect bovine reproduction of Colombia generating abortions, decrease in milk production, loss of animals due to sanitary problems and additional expenses in treatments. This review is a retrospective analysis of the last 10 years in Colombia, where the main diagnostic methods for these reproductive diseases were also mentioned, such as ELISA tests, MAT micro agglutination, Rose bengal and PCR.